Investigating the Difference between Dynamic and retrospective Experiences of the Experiential Marketing of Luxury Fashion Brands - Chiang, Stephen (2014)
Experiential marketing is a new area that has arisen as traditional marketing has become increasingly less able to cater to the modern consumer’s need for their senses to be dazzled and their emotions stimulated. The majority of literature in experiential marketing was founded on consumers’ retrospective experiences, and scarcely paid attention to their dynamic experiences. In observance of this, a seminal paper by Schmitt et al (2009) identified a gap in literature - whether consumers’ dynamic experiences were different from their retrospective experiences - which ultimately served to become the research problem of this study. On the basis that this research found that differences between dynamic and retrospective experiences did indeed exist, further corollary objectives were i) to explore the extent of the differences between dynamic and retrospective experiences, and ii) to find whether experiences are remembered more favourably or less favourably over time. This study undertook these research objectives within the context of luxury fashion brands in Hong Kong, China. The study will be measured utilising an adapted version of Schmitt et al’s (2009) dimensions of experiential marketing. Following the collection of data from questionnaires distributed to luxury fashion brand consumers in Hong Kong, a paired t-test revealed that a difference between dynamic and retrospective experiences did indeed exist. Subsequently, social identity, sensory and intellectual experiences were found to reveal relatively low degrees of differences between their dynamic and retrospective experiences, while emotion experiences and behavioural experiences were recorded to have a comparatively larger difference. Furthermore, a paired t-test also indicated that consumers’ reported that sensory, emotion, intellectual and behavioural experiences were remembered less favourably in their retrospective accounts compared to their dyanmic experiences, whereas social identity experiences were revealed to be more favourably remembered by consumers over times. In extension to these findings, this study made a contribution to both a theoretical and practical contribution by putting forward several recommendations to experiential marketing and marketers. Moreover, areas for future research were outlined, and key limitations of the study were made clear.